2023
DOI: 10.1177/15353702221147560
|View full text |Cite
|
Sign up to set email alerts
|

Corilagin alleviates intestinal ischemia/reperfusion injury by relieving oxidative stress and apoptosis via AMPK/Sirt1-autophagy pathway

Abstract: Intestinal ischemia/reperfusion (II/R) injury is a common pathological process with high clinical morbidity and mortality. Autophagy plays an important role in the pathological development of II/R. Corilagin (CA) is a natural ellagitannin with various pharmacological effects such as autophagy regulation, antioxidant, and antiapoptosis. However, whether CA alleviates II/R injury is still unclear. In this study, we had found that CA significantly attenuated II/R induced intestinal tissue pathological damage, oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Several related genes, such as MMP series proteins and SMA, are affected by this signaling pathway. [18][19][20] However, some limitations were observed to this study, such as lack of detailed molecular mechanism analysis. Next, we should carefully analyze the downstream proteins of corilagin that inhibit progression of asthma through AMPK, which can be analyzed and identified by multi-omics (different omic groups) methods.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several related genes, such as MMP series proteins and SMA, are affected by this signaling pathway. [18][19][20] However, some limitations were observed to this study, such as lack of detailed molecular mechanism analysis. Next, we should carefully analyze the downstream proteins of corilagin that inhibit progression of asthma through AMPK, which can be analyzed and identified by multi-omics (different omic groups) methods.…”
Section: Discussionmentioning
confidence: 96%
“…It exerts NF-κB inhibitory activity through phosphorylation of its downstream target proteins, thereby blocking the process of inflammatory response and alleviating asthma manifestations. 18 AMPK consists of a catalytic subunit and two regulatory subunits, which mainly regulate cellular energy metabolism. Emerging evidence supports that AMPK acts as a "metabolic brake" on energy-expenditure processes that drive inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that selenium nanoparticles can effectively alleviate intestinal epithelial barrier damage by inhibiting autophagy mediated by the TBC1D15/Rab7 signaling pathway[ 45 ]. In contrast to the above studies, activation of the AMPK/ SIRT1-autophagy pathway alleviated intestinal I/R injury[ 46 , 47 ]. These studies seem to suggest that autophagic changes during the ischemic phase play a more decisive role in the course of the disease.…”
Section: Autophagy and Gi Diseasesmentioning
confidence: 90%
“…Likewise, Oroxylin A, an active constituent of Scutellaria baicalensis, can regulate ferritinophagy and inhibit hepatic fibrosis via the cGAS-STING pathway [ 120 ]. In addition, some potent compounds, such as Corilagin, have anti-inflammatory and antioxidant effects [ 121 , 122 ], Wang et al found that Corilagin could inhibit NCOA4-mediated ferritinophagy, regulate iron homeostasis, inhibit ferroptosis, and attenuate intestinal ischemia/reperfusion injury (IIRI) in mice [ 123 ]. A coumarin derivative extracted from a variety of plants, Esculetin (6,7-dihydroxycoumarin), was shown to induce ferritinophagy in hepatocellular carcinoma cells through the NCOA4/LC3II/FTH1 pathway, promoting ferroptosis and exerting anticancer effects [ 124 ].…”
Section: Therapeutic Approaches To Target Ferritinophagymentioning
confidence: 99%